The PHASE ANGLE AND ITS CLINICAL RELEVANCE TO MALNUTRITION AND LOW-GRADE INFLAMMATION AMONG HEMODIALYSIS PATIENTS: A CROSS-SECTIONAL PERSPECTIVE - WIDIASIH, ESTI (Perhimpunan Dokter Gizi Klinik Indonesia, 2026)
Background: Patients with chronic kidney disease (CKD) undergoing routine hemodialysis are prone to chronic inflammation and malnutrition, two interrelated conditions that worsen clinical outcomes. The phase angle obtained from bioelectrical impedance analysis (BIA) reflects cell membrane integrity and nutritional status and is suspected to correlate with inflammatory biomarkers such as TNF-α. Objective: To analyze the relationship between phase angle and Dialysis Malnutrition Score (DMS) on TNF-α levels in routine hemodialysis patients. Methods: A cross-sectional analytical study was conducted on 50 routine hemodialysis patients in a clinic in Semarang. Data collected included age, sex, duration of hemodialysis, BMI, skeletal muscle mass (SMM), DMS, phase angle, and TNF-α levels. Data were analyzed using Pearson correlation and multiple linear regression. Results: The average age of participants was 52.38 years, and the average phase angle was 5.05. Pearson correlation showed a significant negative correlation between phase angle and TNF-α levels (r = -0.587; p = 0.000), while DMS showed a positive correlation (r = 0.368; p = 0.009). In the regression model, only phase angle was a significant predictor of TNF-α (β = -0.471; p < 0.001). Conclusion: Phase angle has a significant negative correlation with TNF-α levels, suggesting its potential as a non-invasive marker for inflammation monitoring in hemodialysis patients. DMS was not significant in the multivariate model. Further studies are recommended to explore causal relationships and longitudinal assessments. Keyword : Hemodialysis, Phase Angle, TNF-α, Malnutrition, DMS, Chronic Inflammation